ESTUDIO DE LOS FACTORES QUE INCIDEN EN LA FUGA DE INFORMACIÓN DIGITAL EN LA RED DEL GAD MUNICIPAL DEL CANTON JUJAN - Solis Tobar, Estiven Joel (2019)
The Alfredo Baquerizo Moreno canton (JUJAN), is located northwest of the province of Guayas, 60 km from Guayaquil, its height is 9m above sea level, the temperature ranges between 24 and 25 degrees Celsius, has a population of 25,179 inhabitants. Its economy is based on the agriculture of products such as: Rice, Cocoa, Sugar Cane, Corn, Banana, soy and short-cycle foods. The Municipal GAD of the Cantón Alfredo Baquerizo Moreno (Jujan), is located in the streets Jaime Roldos aguilera # 313 and José Domingo Delgado. Its Mission is that the Municipal Autonomous Decentralized Government of A.B.M "JUJAN" contributes to the society of the Canton of Montecristi by providing public works and services good quality in an equitable way respecting biodiversity and cultural diversity in attainment of good living; In addition, it works with transparency and creates spaces for protagonist participation of citizens in decision-making in the fields sociocultural, environmental, economic and political institutional, with what promotes the development cantonal planning and sustainable canton in the short medium and long term. Its Vision is that the Municipal Autonomous Decentralized Government of A.B.M. "JUJAN", it will be an example of local development with a trained staff that works planned mind based on principles and values ​​such as solidarity, honesty, responsibility; is a institution that performs sustainable and efficient self-management; promotes the participation of citizenship for the effective and equitable distribution of resources; their services are of quality and works transparently; its actions allow the preservation of the environment, cultural diversity, gender and generational equity, making it a municipality for all and all. In the Municipal GAD (JUJAN) it obtains daily information from all citizens who reside in the canton, these data are stored in the servers which can be find vulnerable, because data networks are increasingly useful and important for any entity, it is necessary to know the vulnerabilities and the factors with which could come to fruition resulting in the creation of problems that could cause the malfunction of the network.